Jacob Read papers - Read, Jacob, 1752-1816.
Correspondence, commission, military orders, legal and financial papers chiefly from the years Read served as delegate to the U.S. Continental Congress (1783-1786). Subjects include the Revolution, confiscation of Loyalist property, the Peace of Paris (1783), and politics in South Carolina. Correspondents include Richard Peters and Jacob Read's brother, William.
In part, transcripts.
Delegate to the U.S. Continental Congress, U.S. senator, and army officer of South Carolina.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Peters, Richard, -- 1743-1828 -- Correspondence; Read, William, -- 1754-1845 -- Correspondence; Great Britain. -- 1783 September 3.; United States. -- Continental Congress; American loyalists; South Carolina -- Politics and government -- 1775-1865.; United States -- History -- Revolution, 1775-1783.; Army officers; Delegates, U.S. Continental Congress -- South Carolina; Senators, U.S. Congress -- South Carolina